PENERAPAN TEKNIK SPIRITUAL EMOTIONAL BREATHING (SEB) SEBAGAI METODE DALAM MENINGKATKAN FUNGSI RESPIRASI PADA PASIEN TUBERCULOSIS PARU: THE EFFECT OF SPIRITUAL EMOTIONAL BREATHING (SEB) TECHNIQUE AS A METHOD TO IMPROVE RESPIRATORY FUNCTION IN PATIENTS WITH PULMONARY TUBERCULOSIS - Loya, Sindi Rambu Podu; Santoso, Shelfi Dwi Retnani Putri; Irma; Ledju, Asrial; Ora, Anderias Tara Watu; Agustine, Uly; Paju, Wanto (WELL BEING, 2024)
Pulmonary tuberculosis (TB) is one of the leading causes of death from infections worldwide. Pulmonary TB is caused by the bacterium Mycobacterium tuberculosis, which can cause inflammation affecting the lung parenchyma. The entry of the bacteria triggers an inflammatory response that damages the alveolar-capillary membrane, leading to impaired lung expansion due to fluid accumulation, which in turn affects respiratory system function. To address respiratory function issues in pulmonary TB, one solution is the application of spiritual emotional breathing (SEB). This study aims to determine the effect of the SEB technique on optimizing respiratory function in pulmonary TB patients. The design used is a quasi-experimental design with a one-group pre-test and post-test with control group design. The sample consisted of 40 respondents, divided into 2 groups: control and intervention, each with 20 respondents, selected using convenience sampling. The intervention provided was SEB according to the SOP, and the measurement of RR and SpO2 was conducted using observation and oximetry. Data analysis was performed using t-tests and Wilcoxon tests. The results showed p = 0.251 in the treatment group and p = 0.353 in the control group, indicating that this intervention did not have a significant effect on RR. However, the SpO2 results showed p = 0.001 in the treatment group, indicating a significant effect of SEB on SpO2, whereas p = 0.518 in the control group. SEB improves respiration, such as lung capacity and gas exchange.